High power printed circuit board design for automotive fuse block usage (2017)
The minimal size for the conductor calculation is always the first point of interest when an electrical designer is creating a High Power Printed Circuit Board for automotive applications; in this paper you will see the factors considered to calculate the conductor size, the math information, the background information for the factors selection and the conservative rules implemented to protect the circuits for an overload; in addition this document shows two different methods to define the conductor size for the Printed Circuit Board, one based in international standards (Actual Design) and the other based in design assumptions defined to reduce the conservative rules used to calculate the conductor size (Proposal Design). In addition, you can see the validation data and the statistical results to support the implementation for the proposal method in the fuse block design used in the automotive industry, due the Proposal Design provides High Power Printed Circuit Boards with 33% less copper compared to the Actual Design.